Penggunaan Dan Pemanfaatan Wordpress Dalam Upaya Meningkatkan Daya Jual Untuk Pelaku UMKM Karang Taruna Bojongkulur - Neneng Rachmalia Feta; Ninuk Wiliani; Rizki Hesananda (LPPM Universitas Nusa Mandiri, 2021)
The advancement of digital technology has helped many people in every aspect of their lives. One of them is the web, which is also a tool that has been widely used to share information by the public. However, the utilization has not been maximized, especially among the lower-class communities in rural areas and UMKM. Bojongkulur youth organization is one of the youth organizations engaged in social welfare, located in the village of Bojongkulur, Gunung Putri sub-district, Bogor Regency. Bojongkulur youth organization consists of local youths, most of whom are MSME actors. This partner was chosen in line with the vision and mission of the Bank Rakyat Indonesia Institute of Technology and Business, which is to support the development of MSMEs through the use of information technology. Therefore, training on web creation and management of WordPress-based web content was given to the Bojongkulur youth organization to help them manage the web to build their brand and market their products. Training on the use and utilization of WordPress begins with the provision of material about what WordPress is, then the training is continued with the practice of making WordPress for each UMKM actor. The practice starts from creating the email, how to register domains and choosing a website address name, and creating content on the dashboard, post pages, categories, tags, media, comment pages, views, plugins, user pages, website settings, website preview to the stage of launching a website. . Broadly speaking, this training makes e-commerce with the WordPress content management system.